PROPAGANDA: DODELIKE WAPEN VAN DIE KOMMUNISME - C. Nelson (Scientia Militaria, 2012)
During the Second World War the effectiveness and importance of the applicetionof propaganda in influencing a mess society became evident. Under the influence ofHitlet and his follower Joseph Goebbels the use of propaganda was developed intoa fine art and was systematically used to convey Nazi ideas to the uninformed masses.Nowadays this seme weapon is used by the Communists to extend their influencebeyond the borders of the Soviet Union. Propaganda may be seen as the deliberate attempt by an individual or group. toinfluence another person or group so that in a given situation the reaction of theinfluenced person will be that desired by the group. It is not always possible toinfluence everyone, as people identified as 'nuclear-personalities' have certain attitudesof long standing which they are normally not apt to surrender. The great masses,however, are 'uninformed stuff' and have no strong opinions of their own, but tendto be guided by their need to belong to a group. Hence their opinions are determinedby those of the group. It is towards reaching the group - the masses - that thepropaganda programme is directed. By means of the radio, newspapers, and othermedia certain ideas are transplanted beyond their borders. This process is usually80 ingeniously conducted that the groups influenced are not aware of it. One of thereasons why they are ceught unawares may be attributed to the fact that the propagandistconfronts them with certain ideas on nationalism or peace which are acceptedby the group. Under this cover the real motives - in this cese the Communist valuesand way of thinking - are conveyed. It is in these hidden and underlying motivesthat the real threat to any state lies, as the bulk of its society is gradually indoctrinatedto come to accept certain Communistic principles, giving the Communist Governmentthe opportunity to extend its sphere of influence and mainstay over another govemment.In this fashion countries are subjugated without any wars being fought.